2021
DOI: 10.1097/rhu.0000000000001772
|View full text |Cite
|
Sign up to set email alerts
|

Low-Density Granulocytes and Neutrophil Extracellular Traps as Biomarkers of Disease Activity in Adult Inflammatory Myopathies

Abstract: Background/Objective: Biomarkers for disease activity and damage accrual in idiopathic inflammatory myopathies (IIMs) are currently lacking. The purpose of this cross-sectional study is to analyze the relationship among low-density granulocytes (LDGs), neutrophil extracellular traps (NETs), and clinical and immunological features of patients with IIM. Methods:We assessed disease activity, damage accrual, amount of LDGs, NETs, expression of LL-37, and serum cytokines in 65 adult patients with IIM. Differences b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…These phenomena mimic the role of the BM neutrophils in vivo in the pathogenesis of CIA. Some literature has reported that serum rich in inflammatory cytokines and autoantibodies from individuals with different diseases can induce NETs formation in vitro, 30‐33 while normal serum may inhibit NETs formation 34 . Different results of NETs induction by different serum may also indicate the role of environmental components in neutrophil activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These phenomena mimic the role of the BM neutrophils in vivo in the pathogenesis of CIA. Some literature has reported that serum rich in inflammatory cytokines and autoantibodies from individuals with different diseases can induce NETs formation in vitro, 30‐33 while normal serum may inhibit NETs formation 34 . Different results of NETs induction by different serum may also indicate the role of environmental components in neutrophil activation.…”
Section: Discussionmentioning
confidence: 99%
“…These phenomena mimic the role of the BM neutrophils in vivo in the pathogenesis of CIA. Some literature has reported that serum rich in inflammatory cytokines and autoantibodies from individuals with different diseases can induce NETs formation in vitro,[30][31][32][33] while normal serum may inhibit NETsF I G U R E 6 Impaired maturity of bone marrow (BM) neutrophils from granulocyte colony-stimulating factor (G-CSF)−/− mice. A, Representative dot plots of the relative proportion of mature neutrophils.…”
mentioning
confidence: 99%
“…Circulating NETs were reported to be associated with higher levels of anti-MDA5 antibody and skin disease activity [ 30 ]. Low-density granulocytes and NETs containing LL-37 were also increased in patients with IIM and active disease and correlate with proinflammatory cytokines [ 8 ]. IIM NETs decreased the viability of myotubes in a citrullinated histone-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other specific biological forms or associated factors of neutrophils, like neutrophil extracellular traps (NETs), may also play an important role in IIM. NETs containing human cathelicidin were reported to be increased in patients with IIM and active disease and correlate with proinflammatory cytokines [ 8 ]. Peripheral NET levels are associated with calcinosis and interleukin (IL)-8 levels [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low-density neutrophils or LDG gene signatures have also been observed in many other immune-mediated disorders, including IIM, RA, juvenile idiopathic arthritis, and Pyogenic arthritis, pyoderma gangrenosum, and acne (PAPA) syndrome [ 9 , 30 , 65 , 83 86 ]. The classical enhancement of spontaneous NET formation has been observed in LDGs from IIM, PAPA syndrome, and equine asthma.…”
Section: Role Of Ldgs In Immune-mediated Inflammatory Diseasesmentioning
confidence: 99%